Fabrication And Machining Performance Of Ceramic Cutting Tool Based On The Al2O3-ZrO2-Cr2O3 Compositions - Abu Bakar, Mohd Hadzley; Tamin, Nor Fauzi; Azhar, Anis Afuza; Mokhtar, Muhammad Faiz; Hamed, Muhammad Fitri Naim; Azlan, Umar Al-Amani (Elsevier Editora Ltda, 2019)
This study presents the cutting tool development of zirconia toughened alumina (ZTA) with chromia addition. The process used for its development is solid-state, in which the powders of Alumina (Al2O3), Zirconia (ZrO2) and Chromia (Cr2O3) were processed by a ball mill, compacted under a Cold Isostatic Press (CIP) and sintered at a constant temperature of 1400 °C with 9 h soaking time. The initial study investigated the effect of Polyethylene glycol (PEG) as a binder, CIP and hardness of Al2O3-ZrO2 mixtures. The percentage composition between Al2O3 and ZrO2 was varied to choose the best for the highest mechanical performances determined by the density, porosity and properties analysis. The cutting tool that possessed the highest hardness and bending strength was selected the Al2O3-ZrO2 mixture was mixed 0.6 wt% Cr2O3 for machining trials within the cutting speed of 200-350 m/min and constant feed rate and depth of cut of 0.150 mm/rev and 0.5 mm, respectively. The results of the ZTA mixed with Cr2O3 and combined with the ratio 80-20-0.6 wt% showed that the addition of 0.6 wt% PEG and a CIP pressure at 300 MPa and 60 s dwell time resulted maximum hardness and bending strength of 71.03 HRc and 856.02 MPa, respectively. The fabricated cutting tool was capable to reach 225 s tool life when machining AISI 1045 at a lower cutting speed of 200 m/min and higher feed rate of 0.150 mm/rev.